Purchasing power parity in the Czech Republic and Slovenia - Boršič, Darja (Naše gospodarstvo, 2007)
In this paper we test the theory of purchasing power parity for the Czech Republic and Slovenia in comparison to Austria, Germany, France and Italy by employing data from January 1992 to December 2001. Results of unit root tests indicate that the eight time series of the real exchange rates of the koruna and the tolar are integrated of order one. Though some cointegration was found among the nominal exchange rates and selected consumer price indices, the presented results do not support the theory of purchasing power parity in any of the two observed economies.
Keywords: Slovenia; Slovenija; Czech Republic; Češka; denar; kupna moč; pariteta; devizni tečaj